ENVIRONMENTAL RISK ASSESSMENT OF FOUR CONVENTIONAL PESTICIDES ON THE POLLINATOR Forcipomyia spp. (DIPTERA: CERATOPOGONIDAE) OF CACAO CULTIVATION (THEOBROMA CACAO), IN SAN MARTÍN, PERU - SOTOMAYOR-CHAVEZ, Astrid (2024)
The cocoa crop (Theobroma cacao), is pollinated mainly by Forcipomyia spp. (Diptera: Ceratopogonidae). The objective was to evaluate the environmental risk of four conventional pesticides: cypermethrin, carbofuran, copper oxychloride and chlorpyrifos, used in the cultivation of cocoa on the pollinator, Forcipomyia spp. The environmental risk was evaluated by analyzing the abundance index of Forcipomyia in the town of Sangamayoc, Barranquita district, Lamas province, San Martín region, Peru. The individuals were obtained by incubation and capture in emergency boxes with cocoa litter that encountered the four pesticides over three evaluations. The results show that chlorpyrifos presented the highest environmental risk on the abundance of Forcipomyia, followed by cypermethrin, carbofuran and copper oxychloride. In the first evaluation, a decrease in pollinator abundance was observed, followed by a slight recovery in subsequent evaluations. It is concluded that chlorpyrifos had the greatest effect on the abundance of Forcipomyia, and copper oxychloride the one with the least effect. Forcipomyia proved to be an adequate indicator for the evaluation of environmental risk due to the application of pesticides.